Answer:
Step-by-step explanation:
Let say; By y(x)= y(e)
we have;
Using Fundamental Theorem of Calculus and differentiating by Lebiniz Rule:
dy/dx = 1/xy
RECALL: y(e) = 3
MULTIPLYING BOTH SIDE BY 2 , TO ELIMINATE THE DENOMINATOR, WE HAVE;
Answer: 23
Step-by-step explanation: a P e X
Part (i)
Plug in theta = pi/3 to get
h(theta) = sin(3theta)
h(pi/3) = sin(3*pi/3)
h(pi/3) = sin(pi)
h(pi/3) = 0 ... use a calculator or the unit circle
<h3>Answer: 0</h3>
=================================================
Part (ii)
Plug in h = pi/2
h(theta) = sin(3theta)
h(pi/2) = sin(3pi/2)
h(pi/2) = -1
<h3>Answer: -1</h3>
Answer:
y=1/3x_1/5=1/3×15=5_1/5×15=3. 5_3=2
Answer: 5-10g+20h
Step-by-step explanation:
You can rewrite as 5(1-2g+4h). 5x1 equals 5, 5x2g=10g, 5x4h=20h, then you get 5-10g+20h
-viridiancat4, an 8th grader! :)